Quality of statistical match used in the estimation of the Levy Institute Measure of Time and Income Poverty (LIMTIP) for Italy 2008 and 2014 and preliminary results - Erica Aloè (Levy Economics Institute of Bard College, 2020)
This paper assesses the quality of the statistical matching used in the LIMTIP estimates for Italy for 2008 and 2014. The match combines the 2008-9 and 2013-14 Italian Time Use Survey (IT-TUS) with the Italian data collected for the European Survey on Income and Living Conditions (IT-SILC) in 2009 and 2015. After the matching, the analysis of the joint distributions of the variables shows that the quality is good. The preliminary results of the LIMTIP estimates in Italy display widespread time poverty, which translates into significant hidden poverty. The LIMTIP also reveals that the increase in the poverty rate between 2008 and 2014 was even higher that what standard poverty measures report.
Keywords: C14; C40; D31; J22; 330; Statistical Matching; Time Use; Household Production; Poverty; LIMTIP; Italy